Development and validation of a high‐performance liquid chromatography–tandem mass spectrometric method for simultaneous determination of bupropion, quetiapine and escitalopram in human plasma. (29th September 2014) - Park, Semin; Park, Chul‐Soo; Lee, Sung Joong; Cha, Boseok; Cho, Young Ah; Song, Yi; Yu, Eun Ae; Kim, Gon‐Sup; Jin, Jong Sung; Abd El‐Aty, A. M.; El‐Banna, H. A.; Hacımüftüoğlu, Ahmet; et al.
Abstract: In the present study, an effective high performance liquid chromatography–tandem mass spectrometric (HPLC/MS/MS) method was developed and validated to simultaneously determine bupropion (BUP), quetiapine (QUE) and escitalopram (ESC) in human plasma using carbidopa as the internal standard. Chromatographic separation was achieved on a Waters Sun Fire C18 column using reversed‐phase chromatography. The MS/MS experiment was performed in positive ion multiple reaction monitoring mode to produce product ions of m/z 240.3 → 184.2 for BUP, 384.2 → 253.1 for QUE, 325.3 → 109.3 for ESC and 227.2 → 181.2 for the internal standard. The method showed good linearity ( R 2  ≥ 0.997), precision (relative standard deviation ≤7.5%), satisfactory intra‐ and interday accuracy (88.4–113.0%) and acceptable extraction recovery (87.2–115.0%), matrix effect (84.5.5−108.7%) and stability (92.3−103.5%). The method was successfully applied to determine the concentrations of BUP, QUE and ESC in human plasma samples. Copyright © 2014 John Wiley & Sons, Ltd.